ISLAMIC ECONOMICS: THOUGHT STUDY OF MASUDUL ALAM CHOUDURY - Imam Taufiq; Moh Harman Eko Santoso; Azidni Rofiqo (Journal of Islamic Economics and Philanthropy, 2021)
The discussion of Islamic Economics is always interesting to study. Its existence and development are subject to many researches, including the thoughts and ideas of Islamic economic thinkers. This paper attempts to describe the works and thought patterns of Masudul Alam Choudury in the field of Islamic economics. Qualitative approach through literature review from various sources is used in this study. The findings in this paper explain that the Islamic Economy according to the Masudul Alam Choudury is a new economic order which is a solution for conventional economic inability to realize prosperity. Masadul Alam Choudury also underlines the current Islamic Economy which only contributes to the diversity of market products.